Ankle-Brachial Index Assessment: Does it Matter how arm Pressures are Measured?. Issue 2 (June 2013) - Lear-Rayborn, Elisa; Matsuura, John H.; Pehde, Colin; Perkins, Samantha; Barkema, Karla; Wiarda, Christy; Hall, Andrew; Wobst, Garrett; Geletta, Simon; Pehde, Colin
Introduction: —The ankle-brachial index (ABI) is an essential tool used not only in screening for peripheral artery disease (PAD) but also in deciding treatment options of the patient with known PAD. Most vascular laboratories have standardized testing, i.e., Doppler measurement of the arm and ankle pressures in ABI calculation. However, some centers still rely on auscultation with a stethoscope to measure arm pressure. This study sought to determine any differences in ABI calculation between the two techniques. Methods: —Permission for the study was obtained by the Institutional Review Boards of Des Moines University and the Iowa Heath-Des Moines System. We first calculated the ABI in a group of 50 healthy volunteers with no history of PAD (control group) by using both Doppler arm pressure and stethoscope arm pressure and Doppler-derived ankle pressures. This represented our "normal" population. We enrolled patients in two Intersocietal Commission for the Accreditation of Vascular Laboratories–accredited Vascular Laboratories at the Iowa Methodist Medical Center (Des Moines, IA) and the Iowa Clinic (West Des Moines, IA) to perform similar Doppler and stethoscope arm pressure and Doppler ankle pressures for ABI determinations in 50 patients (study group). Results: —In the comparison group of healthy volunteers, the mean Doppler ABI was 1.18 ± 0.17 in the left leg and 1.22 ± 0.21 in the right leg. Using stethoscope arm pressure measurement, we found that the mean left leg ABI was 1.18 ± 0.17 and 1.17 ± 0.20 in the right leg. The study group of patients showed a Doppler arm pressure determination of ABI in the left leg of 1.02 ± 0.24 and 1.02 ± 0.23 in the right leg. Stethoscope ABI calculation for the study patients showed a mean left leg ABI of 1.03 ± 0.24 and in the right leg of 1.04 ± 0.24. A test–retest reliability analysis was then performed via the parallel model. Cronbach's alpha was then calculated to ascertain the level of agreement between the two ABI data sets (Doppler versus stethoscope ABI) in both the control and study patient groups. The equality of variance was confirmed by the chi-squared test (χ 2 = 0.532, df = 1, p > 0.05) for the patient group and 0.972 for the normal population (df = 1, p > 0.05) indicating equal variance in both groups and therefore no difference between test results by method of arm blood pressure assessment. The reliability scale estimate was alpha = 0.99 for the patients and alpha = 0.90 for the normal comparison group, confirming a high degree of correspondence between the two measurement approaches. There was a tendency toward a greater degree of variance in the comparison group of healthy volunteers. Testing was performed by less-experienced, third-year podiatry medical students and may reflect an "experience" factor in measuring ankle and arm pressures, but the differences were not statistically significant. Conclusions: —Our study showed very little difference in ABI calculation between Doppler versus stethoscope determination of the highest arm pressure. It appears that both techniques produced similar results. On the basis of our findings, ABI calculations can be performed with the use of either technique, provided they are standardized to one method of arm pressure determination.